APLIKASI PANDUAN PESTISIDA PADA TANAMAN PADI BERBASIS ANDROID - M. Yusuf, Andi; Syamsuddin, Sumantri (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Rice is one of the food commodity crops that must be available. Various efforts have been made to increase rice productivity in Indonesia, one of which is agricultural intensification. with the condition that the pest population has reached its economic threshold, so this study takes the problem of the application of pesticide guides to android-based rice plants. The research method used is Field Research. The results of testing using Black Box, it is found that the functional application runs well according to the design made. While the results of the White Box test by testing the program algorithm, it is found that the number of flowgraphs with the number of paths in the white box test has the same value, namely V(G) = 6, Predicate (P) = 6 and Region (R) = 6 so it is stated that the programming logic is in accordance with the previous design.